Pertumbuhan Bibit F2 Jamur Tiram pada Berbagai Komposisi Media - Zarmiyeni Zarmiyeni (Rawa Sains: Jurnal Sains STIPER Amuntai, 2016)
Oyster mushroom (Pleurotus ostreatus) is one type of wood mushroom that is used as a vegetable and processed food. In the cultivation of oyster mushrooms (Pleurotus ostreatus), seeds are a determining factor. This study aims to obtain the best media composition in the growth of oyster mushroom F2 seedlings (Pleurotus ostreatus). The research conducted at the Amuntai STIPER Laboratory from April to June 2013, using a Completely Randomized Design (CRD), with 5 treatments and 4 replications. As a treatment, the composition of media (K) is (k1) 80% corn: 18% sawdust: 1% CaCO3: 1% CaSO4, (k2) 70% corn: 28% sawdust: 1% CaCO3: 1% CaSO4, ( k3) 60% corn: 38% sawdust: 1% CaCO3: 1% CaSO4, (k4) 50% corn: 48% sawdust: 1% CaCO3: 1% CaSO4, (k5) 40% corn: 58% sawdust : 1% CaCO3: 1% CaSO4. Observation data were analyzed by variance and DMRT follow-up at 5% level. The parameters observed were the growth of mycelium horizontally and vertically. The results showed that media composition (k2) 70% corn: 28% sawdust: 1% CaCO3: 1% CaSO4 gave the best results for F2 seedling growth